When two is worse than one: The deleterious impact of multisensory stimulation on response inhibition. - Kuzma Strelnikov (Public Library of Science (PLoS), 2021)
Multisensory facilitation is known to improve the perceptual performances and reaction times of participants in a wide range of tasks, from detection and discrimination to memorization. We asked whether a multimodal signal can similarly improve action inhibition using the stop-signal paradigm. Indeed, consistent with a crossmodal redundant signal effect that relies on multisensory neuronal integration, the threshold for initiating behavioral responses is known for being reached faster with multisensory stimuli. To evaluate whether this phenomenon also occurs for inhibition, we compared stop signals in unimodal (human faces or voices) versus audiovisual modalities in natural or degraded conditions. In contrast to the expected multisensory facilitation, we observed poorer inhibition efficiency in the audiovisual modality compared with the visual and auditory modalities. This result was corroborated by both response probabilities and stop-signal reaction times. The visual modality (faces) was the most effective. This is the first demonstration of an audiovisual impairment in the domain of perception and action. It suggests that when individuals are engaged in a high-level decisional conflict, bimodal stimulation is not processed as a simple multisensory object improving the performance but is perceived as concurrent visual and auditory information. This absence of unity increases task demand and thus impairs the ability to revise the response.